Planes of communicative activity in collaborative writing - Thompson, I (Taylor and Francis, 2012)
In this article I focus on the mediational role of communicative activity in the co-construction of meaning involved when pupils write collaboratively. I explore the developmental nature of peer intermental or social activity within a Zone of Proximal Development (ZPD) by drawing on perspectives from sociocultural theory and the dialogical aspects of some classroom activity. Vygotsky’s concept of the ZPD is viewed as a tool used to produce forms of instruction that lead pupils’ psychological development. I identify three planes of communicative activity relating to physical, semiotic and intrapersonal tool usage in order to develop an analysis of two secondary school pupils involved in the shared activity of producing a co-constructed text.